Mediating effect of social interaction anxiety between emotional intelligence and life satisfaction in physical education students: post-COVID-19 study - Calleja-Núñez, Juan José; Granero-Gallegos, Antonio; Espinoza-Gutiérrez, Roberto; Baños, Raúl (Frontiers in Psychology, 2023)
The aim of this research is to analyze the effect of social interaction anxiety on satisfaction with life mediated by emotional intelligence. The research design was descriptive, cross-sectional, and nonrandomized. In total, 1164 Mexican physical education students participated (Mage=21.21; SD=3.26) (30.0% female; 69.6% male; 0.4% other). The scales used were the Social Interaction Anxiety Scale, Trait Meta-Mood Scale and Satisfaction with Life and a structural equation analysis with latent variables was conducted. The results highlight that it can be asserted that emotional clarity and repair had a mediating effect between social interaction anxiety and satisfaction with life, as they did decrease the negative effects of social interaction anxiety on satisfaction with life. In addition, social interaction anxiety had a direct and positive effect on emotional attention and a negative effect on emotional clarity and repair.